(untitled) - Brezonik, Patrick L. (Boca Raton, 1994)
Chemical Kinetics and Process Dynamics in Aquatic Systems is devoted to chemical reactions and biogeochemical processes in aquatic systems. The book provides a thorough analysis of the principles, mathematics, and analytical tools used in chemical, microbial, and reactor kinetics. It also presents a comprehensive, up-to-date description of the kinetics of important chemical processes in aquatic environments. Aquatic photochemistry and correlation methods (e.g., LFERs and QSARs) to predict process rates are covered. Numerous examples are included, and each chapter has a detailed bibliography and problems sets. The book will be an excellent text/reference for professionals and students in such fields as aquatic chemistry, limnology, aqueous geochemistry, microbial ecology, marine science, environmental and water resources engineering, and geochemistry.
Keywords: Water chemistry,Chemical kinetics